Necrotizing Fasciitis of the Hand: Management with Literature Review - Delavari, Sarina; Megas, Ioannis Fivos; Billner, Moritz; Reichert, Bert; Breidung, David (Plastic and Reconstructive Surgery Global Open, 2024)
This report presents a case of necrotizing fasciitis following a seemingly minor injury sustained from handling a spiny plant. Despite initial primary care by a physician, the patient presented with severe septic shock and necrotizing fasciitis of the hand, necessitating emergency surgical intervention. The use of scoring systems aided in the prompt recognition of the condition. Subsequent surgery was required due to infection progression, leading to significant soft tissue defects and functional impairment. The patient underwent multiple reconstructive procedures, including placement of dermis-replacement material and, ultimately, free flap reconstruction, to restore the hand function. This case report highlights the importance of rapid identification of potential cases of necrotizing fasciitis in cases of hand infections, demonstrates that scoring systems can assist in smaller affected body sites such as the hand, and illustrates the difficulties of defect reconstruction following necrotizing fasciitis.
CRIS-Team Scopus Importer:2024-08-02